Spontaneous uterine rupture at 22 weeks’ gestation in a multipara with previous hysteroscopic resection of fibroid - Badial, Gurbaksh (BMJ Publishing Group, 2012)
A 34-year-old multiparous woman presented at 22(+6) weeks’ gestation with severe abdominal pain which preceded a mechanical fall down the stairs. On admission, fetal movements were felt and fetal heart rate was detected by Doppler ultrasound. Over the course of 12 h, although she maintained her vital signs, repeat laboratory and radiological investigations suggested sinister intra-abdominal pathology. Subsequently, fetal movements and heart rate ceased and the patient began to decompensate. A CT scan confirmed uterine rupture. Subsequent emergency laparotomy revealed a 2 l haemoperitoneum and lifeless fetoplacental unit in the abdominal cavity. It is postulated that this rupture occurred as a rare yet life-threatening complication of a hysteroscopic resection of fibroid that the patient underwent 1 year previously. There are no known published cases of a spontaneous uterine rupture following a hysteroscopic procedure at such an early gestation. The patient made a full physical recovery.